Right ventricular-vascular coupling in heart failure with preserved ejection fraction and pre- vs. post-capillary pulmonary hypertension. (22nd May 2017) - Gorter, Thomas M; van Veldhuisen, Dirk J; Voors, Adriaan A; Hummel, Yoran M; Lam, Carolyn S P; Berger, Rolf M F; van Melle, Joost P; Hoendermis, Elke S
Abstract: Aims: Many patients with heart failure with preserved ejection fraction (HFpEF) develop post-capillary pulmonary hypertension (PH) due to increased left-sided filling pressures. However, a subset of patients develops combined post- and pre-capillary PH. We studied the value of echocardiographic right-sided characterization for the discrimination between pre- vs. post-capillary PH in HFpEF, using invasive haemodynamics as gold standard. Methods and results: 102 consecutive HFpEF patients with simultaneous right heart catheterization and echocardiography were identified. Patients were divided into: 'no PH', 'isolated post-capillary PH', and 'post- and pre-capillary PH'. Systolic pulmonary arterial pressure (SPAP), tricuspid valve annular plane systolic excursion (TAPSE), right ventricular-vascular coupling (TAPSE/SPAP), and VO2 -max were assessed. Primary endpoint was all-cause mortality. A total of 97 patients were included: 22% no PH, 47% isolated post-capillary PH, and 31% post- and pre-capillary PH. Patients with post- and pre-capillary PH had more often diabetes mellitus (47 vs. 24%, P = 0.04), had more heart failure hospitalizations (57 vs. 26%, P = 0.007) and lower VO2 -max (10 vs. 13 mL/min/kg, P = 0.008), compared with those with isolated post-capillary PH. Patients with post- and pre-capillary PH also had more reduced TAPSE (17 vs. 21 mm, P = 0.001) and TAPSE/SPAP (0.3 vs. 0.5, P < 0.001). TAPSE/SPAP ratio <0.36 had a good accuracy to identify patients with additional pre-capillary PH (C-statistic 0.86, sensitivity 86% and specificity 79%). TAPSE/SPAP ratio was associated with increased mortality (HR 2.51 [95% CI 1.25–5.01], P = 0.009). Conclusion: Abnormal right ventricular-vascular coupling identifies patients with HFpEF and additional pre-capillary PH, and predicts poor outcome in HFpEF.